Prospects and challenges of bio-based phase change materials: An up to date review - Benhorma, A.; Bensenouci, A.; Teggar, M.; Ismail, K.A.R.; Arıcı, M.; Mezaache, E.; Laouer, A.; Lino, F.A.M. (Journal of energy storage, 2024)
In recent years intensive research has been conducted on phase change materials (PCMs) for both energy storage and thermal regulation of equipment and buildings. However, a great number of PCMs are derived from fossil fuel industry such as paraffin. Thus, bio-sourced PCM can be utilized and hence contribute to achieve the sustainability goals. The objective of the present study is to highlight the latest development as well as perspectives of the potential of bio-PCM for improvement of the performance of various thermal applications and draw recommendations that can direct future research. The reviewed literature includes development of bio-based PCMs, determination of their physical and thermal properties, and evaluation of their thermal performance in domestic and industrial applications such as heating, air conditioning, cooling of photovoltaic panels and lithium-ion batteries, water treatment and distillation, inclusion in commercial and domestic refrigerators, food conservation, refrigeration of pharmaceutical products and vaccines. Some drawbacks of bio-based PCMs such as degradation due to microorganisms, thermal and chemical instabilities, and degradation due to cycling and other long-term effects need further research and developments. Finally, these limitations along with other research gaps are highlighted for future consideration. [Display omitted] •Bio-PCM is promising for sustainable buildings, and more investigations are needed to ensure its efficient integration.•Long duration tests with Bio-based PCM are essential to investigate aging and cycling degradations.•Long term chemical stability should be enhanced as some bio-PCMs degrade through thermal cycling.•Bio-wastes can be used as PCMs with promising economic and environmental advantages.•Bio-based PCM are eco friendly, renewable, cheap and equally efficient as common PCM